The Spirit of Prophecy and the Power of Authoritative Preaching in Luke–Acts: A Question of Origins - Turner, Max (New Testament studies, 1992)
In his influential article in TDNT, E. Schweizer was to claimLuke adopts the typically Jewish idea that the Spirit is the Spirit of prophecy…. This may be seen in Lk 4:23–27, where the miraculous signs mentioned in the quotation in v. 18 are specifically rejected as manifestations of the Spirit and only authoritative preaching is regarded as the fulfilment of the prophecy.